Evaluation of UroVysion for Urachal Carcinoma Detection - Hu, Zhiquan; Ke, Chunjin; Liu, Zheng; Zeng, Xing; Li, Song; Xu, Hua; Yang, Chunguang (Frontiers in Medicine, 2020)
Background: Patients with hematuria who are positive for urinary fluorescence in situ hybridization (FISH) are generally considered to have urothelial carcinoma. We determined whether UroVysion FISH could be used for the diagnosis of urachal carcinoma. Methods: Seven cases of urachal carcinoma with haematuria subjected to FISH analysis were retrospectively analyzed in our hospital from May 2012 to November 2019. Paraffin-embedded tissue sections from one FISH-positive and one FISH-negative urachal carcinoma were processed in strict accordance with the instructions of the UroVysion kit. Meanwhile, FISH data from the other 414 hematuria patients were collected as controls. Results: All 7 patients with urachal carcinoma were diagnosed with adenocarcinoma. According to Sheldon stage, six patients had stage IIIa and one patient had stage IVb. The sensitivity and specificity of urinary FISH for the diagnosis of urachal carcinoma were 71.43% (5/7) and 94.61% (281/297), respectively. The rates of polysomy for chromosomes 3 and 7 in positive patients were both 100% (5/5), whereas the rate of polysomy for chromosome 17 was 40% (2/5), and the chromosome 9p21 region (p16) gene deletion rate was 20% (1/5). Histological assessment and cytological FISH were consistent for urachal carcinoma. No significant difference was observed in the diagnostic efficacy between urachal carcinoma and urothelial carcinoma (71.43 vs. 87.18%, P = 0.245). Conclusions: Taken together, UroVysion FISH was found to be positive in a high proportion of pathologically confirmed urachal carcinoma of late stage with hematuria. Its chromosomal aberrations may be different from those of urothelial carcinoma, but more studies are needed to clarify their genetic background. Not all tumors showing abnormalities by FISH are urothelial carcinomas.